EFFICIENCY AND SAFETY OF USING “OZONE” IN THERAPY OF PATIENTS WITH CHRONIC TUBERCULOSIS OF THE MIDDLE EAR IN PATIENTS WITH PULMONARY TUBERCULOSIS (Journal of Science-Innovative Research in Uzbekistan, 2025)
Chronic tuberculosis of the middle ear (CTME) is one of the urgent problems of modern clinical otology and phthisiology. Among the various methods of treating chronic tuberculous otitis media, a rational combination of systemic etiotropic therapy of exposure to the body with local treatment is currently considered. A comparative analysis of the effectiveness of transtepanal injection of a solution of decasan o, oo2% in combination with O3 in special therapeutic regimens is carried out, the advantage of this technique and its mechanism are described. The results of treatment of 20 patients are presented. All patients underwent daily ear toilet, rinsing of the middle ear cavity with antiseptic solutions followed by the introduction of a solution of decasan in combination with ozone. Despite this, in patients of group 1 (9%), group 2 (2.6%), the effect was noted.